Advancements in Chitosan–Anthocyanin Composite Films: Sustainable Food Preservation with Biodegradable Packaging - Le Li; Quanhong Li (Foods)
To mitigate the escalating environmental pollution caused by plastic packaging films and the associated health risks of the migration of microplastics into food, the development of biodegradable food packaging materials has been recognized as an urgent research priority. In this review, recent advancements in chitosan–anthocyanin composite films (C–As) over the past decade are systematically summarized. First, the key antibacterial and antioxidant mechanisms of chitosan and anthocyanins that contribute to their functional properties are elucidated. Next, the influence of anthocyanin incorporation on the physicochemical characteristics of C–As, including mechanical strength, barrier properties, and thermal stability, is examined. Furthermore, the controlled release behavior of anthocyanins within these C–As and their implications for prolonged bioactivity are explored. Finally, the practical applications of these films in preserving fresh food, such as fruits, vegetables, and meat, are discussed. This review provides a comprehensive framework for designing and optimizing chitosan–anthocyanin-based packaging materials, offering valuable insights for developing sustainable, high-performance food preservation strategies with significant industrial and environmental implications.